Peningkatan Hasil Belajar dan Kemampuan Pemecahan Masalah Biologi Siswa SMA melalui Model Problem Based Learning - Yupiter Laoli (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2024)
Biology learning at the senior high school level still faces challenges, particularly low student achievement and problem-solving skills due to the dominance of conventional, teacher-centered approaches that limit active engagement. This study aimed to analyze the improvement of students’ learning outcomes and problem-solving abilities through the implementation of the Problem Based Learning (PBL) model. The study employed a Classroom Action Research design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were eleventh-grade students studying the human excretory system. Data were collected through learning achievement tests, problem-solving tests, and observation sheets of student activities, and were analyzed using descriptive quantitative and qualitative techniques. The results showed that the implementation of PBL improved students’ average learning outcomes from a moderate to a good category, with classical mastery reaching 100%. Students’ problem-solving abilities also increased from a moderate to a good level. In addition, student engagement during the learning process showed a significant improvement. These findings indicate that the Problem Based Learning model is effective in enhancing the overall quality of biology learning.